Jugando me divierto y aprendo la noción de correspondencia - Verastegui Navarro, Ginelda Mary (2019)
The professional proficiency work was titled "Dancing I have fun and I learn the notion of correspondence", the design of the learning activity, the research of the theoretical support in mathematics and the pedagogical support have been elaborated based on bibliographical references, as well as on the application of the knowledge acquired during the years of my professional training and according to my work experience with children._x000D_ The competence developed in the present activity was: Act and think mathematically in situations of quantity; performance: Establishes one-to-one correspondences in everyday situations. The purpose of the activity was: That boys and girls establish the notion of correspondence._x000D_ Children must understand that mathematics is important in the development of learning, because it allows them to develop their thinking and problem-solving skills.